THE GROWING ROLE OF NATURAL GAS IN THE EURASIAN ENERGY GAMES - MAKHMUDOV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2007)
An analysis of the current economic and geopolitical processes on the Eurasian continent shows the growing importance of natural gas in the competitive struggle unfolding among the leading industrial countries and organizations for priority access to primary energy sources.There are many reasons for this keen interest in natural gas. First, the industry’s experts are forecasting a probable change in the traditional structures of world energy consumption in the next few decades due to the anticipated drop in oil production at currently exploited fields, which will have a detrimental effect on the overall world production of this primary energy resource.Despite directly opposite forecasts that rely on positive estimates of land-based, deep sea, and offshore oil reserves, pessimistic moods nevertheless prevail.Moreover, the forecasts of an increase in global energy consumption, the growth rates of which can no longer be fully met by oil as in the past, are another reason for the growing interest in natural gas.Yet one more important reason for this is environmental protection, particularly where the Western political-economic expanse is concerned. Keeping in mind that environmental levers are becoming an important tool in the policy of Western countries, adherence to environmental requirements and preservation of the biosphere could artificially whip up natural gas consumption rates throughout the world. Western environmental organizations are becoming increasingly adamant about reviewing the energy consumption structure of other states and demanding a transfer to more environmentally friendly types of energy.There is talk that natural gas is becoming the frequent focus of attention due to the extreme politicization of the oil factor. According to some data, in recent years political risk has hiked up the price of a barrel of black gold by 75-80%.However, it should be kept in mind that politicization of the natural gas factor is also only a matter of time. It is actually already becoming increasingly clear. There is nothing surprising in this, since it is an objective process characteristic of any sphere that plays a specific role in the development and security of the economic system of a particular state or interstate organization.Several multidirectional trends are promoting and will continue to promote politicization of the gas factor in Eurasia in the next few years.First, this applies to competition among the leading continental economic forces for priority access to gas production and its transportation routes. This rivalry will grow since more and more players are joining the game. Whereas the continental energy development vectors with respect to consumption were dictated in the past by the Western European countries, the Asian economic boom changed the configuration of the market. The recent powerful industrial upswing in Asia caused by China and India’s tempestuous economic growth has already placed the Asian market among the global leaders in terms of oil consumption rates. It appears that South and Southeast Asia will also soon be determining the trends on the global gas market.